1998
DOI: 10.1037/0012-1649.34.2.224
|View full text |Cite
|
Sign up to set email alerts
|

On having complex representations of things: Preschoolers use multiple words for objects and people.

Abstract: Applying several names to an entity (polynomy) reflects the ability to categorize entities in different ways. Two experiments demonstrate preschoolers' abilities to apply multiple labels to representational objects and to people. In Experiment 1, 3-and 4-year-olds labeled representational objects and verified labels for story characters. In both tasks children reliably produced or accepted several words per entity and accepted a high percentage of both class-inclusive and overlapping word pairs. These results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 75 publications
5
62
0
1
Order By: Relevance
“…For example, ice cream can be considered as belonging to both a taxonomic category (dairy products) and a script category (things at a birthday party). Related research has also shown that young children have the ability to refer to a single item with more than one label, for example, saying that a crayon shaped like a dinosaur is both a dinosaur and crayon (Deák & Maratsos, 1998) or that a sponge painted to look like a rock is both a rock and sponge (Hansen & Markman, 2005). The results of Study 1 contribute to this body of research by verifying an additional system of categorization that children can potentially use to flexibly classify and cross-classify a single item.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ice cream can be considered as belonging to both a taxonomic category (dairy products) and a script category (things at a birthday party). Related research has also shown that young children have the ability to refer to a single item with more than one label, for example, saying that a crayon shaped like a dinosaur is both a dinosaur and crayon (Deák & Maratsos, 1998) or that a sponge painted to look like a rock is both a rock and sponge (Hansen & Markman, 2005). The results of Study 1 contribute to this body of research by verifying an additional system of categorization that children can potentially use to flexibly classify and cross-classify a single item.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they accept unfamiliar label pairs (e.g. both crayon and eraser), even for deceptive objects [22,24,25]. Corroborating results from multiple studies and laboratories show that three-year-olds and even twoyear-olds [21] can rapidly shift between representing and describing the appearance and function of an object.…”
Section: Ruling Out Representational Inflexibilitymentioning
confidence: 98%
“…However, these claims are controversial [13,22,29]. Ultimately, the most relevant studies show that three-year-olds can, in natural conversations, flexibly describe misleading appearances and functions of objects.…”
Section: Ruling Out Representational Inflexibilitymentioning
confidence: 99%
See 2 more Smart Citations